Translanguaging und selbstreguliertes Lernen : Mehrsprachigkeit als Ressource für Bildungserfolg - Kart, Aysel (transcript, 2025)
In the educational practice of a globalised society, the targeted use of multilingualism in everyday life as an educational resource is an undeniable necessity for educational success. Aysel Kart brings together insights from the concepts of translanguaging and self-regulated learning and shows how pupils apply their multilingual resources and self-regulated learning strategies when dealing with educational language requirements in secondary school subject teaching. Based on the subjective learning experiences of the pupils, she provides translanguaging-related ideas for action for a resource-oriented and diversity-conscious multilingual educational practice.